2002
DOI: 10.1002/1099-0682(200207)2002:7<1697::aid-ejic1697>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Dihydrogen(olefin)osmium Complexes with (E)-Ph2P(CH2)2CH=CH(CH2)2PPh2

Abstract: Treatment of [OsClH 3 (PPh 3 ) 3 ] with (E)-Ph 2 P(CH 2 ) 2 CH= CH(CH 2 ) 2 PPh 2 produced [OsClH(PPh 3 ){Ph 2 P(CH 2 ) 2 CH= CH(CH 2 ) 2 PPh 2 }], which reacted with HOTf to give the dihydrogen(olefin) complex [OsCl(H 2 )(PPh 3 ){Ph 2 P(CH 2 ) 2 CH= CH(CH 2 ) 2 PPh 2 }]OTf. Treatment of the latter complex with H 2 did not result in hydrogenation of the olefin double bond, but gave the (hydrido)dihydrogen complex [OsH(H 2 )- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Under molecular hydrogen atmosphere, the latter does not undergo the hydrogenation of the C–C double bond but a molecule of hydrogen chloride is removed to form the hydride-dihydrogen [OsH­(η 2 -H 2 )­(PPh 3 )­{Ph 2 P­(CH 2 ) 2 CHCH­(CH 2 ) 2 PPh 2 }]­OTf ( 455 ; d H2 = 0.97 Å), which can be directly prepared from 453 , by reaction with TlOTf under hydrogen atmosphere (Scheme ). DFT calculations suggest that although the hydrogenation of the olefin of 454 is thermodynamically feasible, it is kinetically unfavorable …”
Section: Osmiummentioning
confidence: 64%
See 1 more Smart Citation
“…Under molecular hydrogen atmosphere, the latter does not undergo the hydrogenation of the C–C double bond but a molecule of hydrogen chloride is removed to form the hydride-dihydrogen [OsH­(η 2 -H 2 )­(PPh 3 )­{Ph 2 P­(CH 2 ) 2 CHCH­(CH 2 ) 2 PPh 2 }]­OTf ( 455 ; d H2 = 0.97 Å), which can be directly prepared from 453 , by reaction with TlOTf under hydrogen atmosphere (Scheme ). DFT calculations suggest that although the hydrogenation of the olefin of 454 is thermodynamically feasible, it is kinetically unfavorable …”
Section: Osmiummentioning
confidence: 64%
“…DFT calculations suggest that although the hydrogenation of the olefin of 454 is thermodynamically feasible, it is kinetically unfavorable. 292 Gusev and co-workers have reported chiral polyhydride complexes stabilized by a PC(sp 3 )P-pincer ligand with an additional Fisher-type carbene arm. 293 The previously mentioned behavior of the trihydride 311 is consistent with a marked tendency of this compound to release molecular hydrogen and to form the 14-valence electrons species OsHCl(P i Pr 3 ) 2 (G), which can also be generated from the dichloride-dihydride 315 by means of the elimination of HCl.…”
Section: Complexes With Pincer Ligandsmentioning
confidence: 99%
“…In addition to promoting the dehydrocoupling of amine–boranes, their ability to activate C–H, N–H, and C–N bonds of a wide range of organic molecules, including 2-azetidinones and nucleobases, allows them to interact with organic synthetic chemistry, drug design, and materials science . Although the chemistry of the osmium polyhydrides is rich, the complexes of this type with pincer ligands are a noticeable exception, being reduced to a few complexes with PNP, P­(olefin)­P, and P­(C­(sp 3 ))­P ligands. Recently, we have reported that the reactions of complexes OsCl 2 {xant­(P i Pr 2 ) 2 }­(κ-S-DMSO) (xant­(P i Pr 2 ) 2 = 9,9-dimethyl-4,5-bis­(diisopropylphosphino)­xanthene) and OsCl 2 {dbf­(P i Pr 2 ) 2 }­(κ-S-DMSO) (dbf­(P i Pr 2 ) 2 = 4,6-bis­(diisopropylphosphino)­dibenzofuran) with molecular hydrogen, in the presence of Et 3 N, lead to the classical trihydride derivatives OsH 3 Cl­{xant­(P i Pr 2 ) 2 } and OsH 3 Cl­{dbf­(P i Pr 2 ) 2 } containing a pincer POP ligand.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to promoting the dehydrocoupling of amine−boranes, 13 ability to activate C−H, N−H, and C−N bonds of a wide range of organic molecules, including 2-azetidinones 14 and nucleobases, 15 allows them to interact with organic synthetic chemistry, 16 drug design, 14a and materials science. 17 Although the chemistry of the osmium polyhydrides is rich, the complexes of this type with pincer ligands are a noticeable exception, 10 being reduced to a few complexes with PNP, 18 P(olefin)P, 19 The kinetically controlled formation of molecular hydrogen by the exothermic neutralization of the hydride ion is a process of great interest in connection with the storage of hydrogen in solid materials, which would become a safe and efficient way to store energy for both stationary and mobile applications. 22 This paper shows that the ligand 9,9-dimethyl-4,5-bis-(diisopropylphosphino)xanthene changes its coordination mode to stabilize Kubas type dihydrogens, elongated dihydrogens, compressed dihydrides, and classical hydrides, which act as intermediates to generate molecular hydrogen from H + and H − , in the presence of osmium polyhydrides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In another study on the reactivity of dihydrogen(olefin) complexes with a structural feature of 1 (or A ), the protonation reaction of [OsClH(PPh 3 ){Ph 2 P(CH 2 ) 2 CH=CH(CH 2 ) 2 PPh 2 }] ( 33 ) has been investigated 19. Protonation of 33 with HOTf produces the dihydrogen(olefin) complex [OsCl(H 2 )(PPh 3 ){Ph 2 P(CH 2 ) 2 CH=CH(CH 2 ) 2 PPh 2 }]OTf ( 34 ), which has been characterized by NMR spectroscopy (Scheme ).…”
Section: Discussionmentioning
confidence: 99%